3(-3x+4)+741=-6(-3x+5)+3x

Simple and best practice solution for 3(-3x+4)+741=-6(-3x+5)+3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-3x+4)+741=-6(-3x+5)+3x equation:


Simplifying
3(-3x + 4) + 741 = -6(-3x + 5) + 3x

Reorder the terms:
3(4 + -3x) + 741 = -6(-3x + 5) + 3x
(4 * 3 + -3x * 3) + 741 = -6(-3x + 5) + 3x
(12 + -9x) + 741 = -6(-3x + 5) + 3x

Reorder the terms:
12 + 741 + -9x = -6(-3x + 5) + 3x

Combine like terms: 12 + 741 = 753
753 + -9x = -6(-3x + 5) + 3x

Reorder the terms:
753 + -9x = -6(5 + -3x) + 3x
753 + -9x = (5 * -6 + -3x * -6) + 3x
753 + -9x = (-30 + 18x) + 3x

Combine like terms: 18x + 3x = 21x
753 + -9x = -30 + 21x

Solving
753 + -9x = -30 + 21x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21x' to each side of the equation.
753 + -9x + -21x = -30 + 21x + -21x

Combine like terms: -9x + -21x = -30x
753 + -30x = -30 + 21x + -21x

Combine like terms: 21x + -21x = 0
753 + -30x = -30 + 0
753 + -30x = -30

Add '-753' to each side of the equation.
753 + -753 + -30x = -30 + -753

Combine like terms: 753 + -753 = 0
0 + -30x = -30 + -753
-30x = -30 + -753

Combine like terms: -30 + -753 = -783
-30x = -783

Divide each side by '-30'.
x = 26.1

Simplifying
x = 26.1

See similar equations:

| 6(-1-5v)=-39+3v | | 4(4d-5e+2f)-(5f-6e+2d)=0 | | y=3x^2+x^4 | | -3-6(8n+2)=5n-15 | | 2n-9=4n+5 | | Y-2/7=4x | | 14y-7x=-21 | | -a^2-7a-10=0 | | 1/6s-1/2s-1=45/2 | | -3(8-3n)=7n-36 | | -5(-4x-8)+6x=-5(5x-7)+725 | | 1/6s-1/2s-1=45 | | 5x+4x+15=-12 | | X/7-3=7 | | 5x+4x+15=11 | | Y+2.5=5.5x | | 5x-x^2=-1 | | -5(-4x-8)+6x= | | 29+4p=3p-5(1-7p) | | 12x-14/ge11x-50 | | -7x-5=5(-8x-1) | | -8/w=-6 | | 6w^3+30w^2-18w-90=o | | (7c)/(10)=(9c)/(10) | | 8+7(3a-1)=-a+23 | | 8z-26=-28+9z | | -20y^2-20-41y=0 | | 3y-25=-29+5y | | -3(x+2)=30 | | -32-4p=6(p-7) | | 4(x+10)=3372 | | 0.2x+0.9=0.3-0.1x+0.3x |

Equations solver categories